(untitled) (Carte Romanze, 2020)
The essay is organized in three parts, in the first it takes stock of the studies concerning the birth and development of forensic medicine, in the second it analyzes the privileged situation of Bologna, between the thirteenth and fifteenth centuries, thanks to the presence of important sources such as municipal statutes and maps, In the third one we try to outline the role of the doctors who, as experts, had the task of dictating or compiling these reports for the judge of the city court, finally we examine the stylistic and formal aspects of these reports, focusing in particular on a report in the vernacular of the mid fourteenth century.